The cost of delivering COVID-19 vaccines in Vietnam - Van Minh Nguyen; Flavia Moi; Laura Boonstoppel; Hong Thi Duong; Chien Chinh Vien; Minh Van Hoang (BMC, 2024)
Abstract Background The COVID-19 pandemic affected hundreds of millions of people and lives, and vaccination was the safest and most effective strategy to prevent and mitigate the burden of this disease. The implementation of COVID-19 vaccination in Vietnam in 2021 was unprecedentedly challenging in scale and complexity, yet economic evidence on the cost of delivery vaccines thought the program was lacking. Methods This retrospective costing study utilized a bottom-up, ingredient-based approach to estimate the cost of delivering COVID-19 vaccines in Vietnam in 2021, from a payer perspective. The study included 38 study sites across all administrative and implementation level, including three geographic areas and two delivery strategies, in two provinces, Hanoi and Dak Lak. The study findings were complemented with qualitative interviews with health staff and stakeholders. Results The economic cost to deliver one COVID-19 vaccine dose was $1.73, mostly comprised of opportunity costs ($1.14 per dose) which were driven by labor costs ($1.12 per dose). The delivery cost in urban areas was the highest ($2.02), followed by peri-urban areas ($1.45) and remote areas ($1.37). Delivery costs were higher at temporary sites ($1.78) when compared to facility-based delivery ($1.63). Comparing low-volume and high-volume periods showed that the delivery cost decreased significantly as volume increased, from $5.24 per dose to $1.65 per dose. Conclusions The study estimates the cost of delivering COVID-19 vaccines in Vietnam in 2021. Enabling factors and challenges during the implementation of the program were explored. Study limitations may lead to underestimation of results and reduce generalizability.